PERAN JAMAAH YASINAN SEBAGAI PUSAT PEMBERDAYAAN DAN PENDIDIKAN BERBASIS MASYARAKAT - Mulyono, (Pelangi Ilmu, 2009)
Abstract Yasinan initially represent activity of religious ritual which is generally conducted by moslem society which is organizate to NU, but later with era appearance of santrinisasi in Indonesia at decade 1985-an, role of Yasinan mount to become religious social activity, so that born Jamaah Yasinan. When this Yasinan become jamaah, hence mostly have been formed [by] official member, there is fee, administration, place innings even have nonscheduled other religious social programs of weekly Routine Yasinan. In so many matter, Jamaah Yasinan have effectiveness as conveyor of activity of mission, and other social activity. Hence pursuant to growth of Jamaah Yasinan during the time precisely if role of Jamaah Yasinan developed and improved to become Center Enableness of Society without getting out of activity initialy as activity of religious ritual, religious social and at the same time Center Education Base on Society at Autonomous era of Area and global era in this time